PENGARUH FASILITAS KERJA, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. INTI SUMBER HASIL SEMPURNA GLOBAL KEDAMEAN-GRESIK - Bakhtiar Dwi Affandi; Rahmat Hidayat Kurniawan (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the influence of Work Facilities, Work Enviroment, and Motivation on employee performance. Sampling method using census. The number of samples used in this study were 60 respondents employees atPT. Inti Sumber Hasil Sempuna Global Kedamean-Gresik. The scope of this research is only on variables related toWork Facilities, Work Enviroment, and Motivation. The approach of this research is the quantitative approach method. The data analysis technique of this research uses the Multiple Linear Regression Analysis method with the SPSS version 26.0 application program.